The Relationship Between the Diet Served and The High Rate of Gastritis in Samarinda Police Detainees in East Kalimantan - Fhirawati, Fhirawati; Nurindahsari, Sri; Nugroho, Hadi (Sean Institute, 2022)
Gastritis is inflammation or bleeding of the gastric mucosa that is acute, chronic, diffuse or local. Gastritis is commonly known as